The effects of kefir drink on liver aminotransferases and metabolic indicators in patients with nonalcoholic fatty liver disease: a randomized controlled trial - Farzaneh Mohammadi; Nadia Razmjooei; Mohammad Ali Mohsenpour; Mohammad Ali Nejati; Mohammad Hassan Eftekhari; Najmeh Hejazi (BMC Nutrition)
Abstract Background and aim Probiotics play an important role in the control and treatment of non-alcoholic fatty liver disease (NAFLD). Kefir drink is a fermented beverage and has indicated some beneficial health effects. The aim of this study was to evaluate the effects of kefir drink on liver aminotransferases, anthropometric indices, glycemic index, lipid profile, blood pressure (BP), high sensitivity C-reactive protein, and malondialdehyde in patients with NAFLD. Methods In an 8-week randomized clinical trial, 80 patients with NAFLD were randomized into two groups of 40. After a 2-week run-in period, the groups received a dietary plan and dietary plan plus a cup of kefir drink twice a day (500 cc/d), respectively. Also, demographic, anthropometric, laboratory, BP, dietary intake, and physical activity assessments were analyzed before and after the intervention. Results At last, seventy-two participants completed the study. No significant difference in changes in BP, anthropometric indices, and laboratory data (P > 0.05) except HDL-C (P = 0.02) and fat-free mass (P < 0.001) was observed between the two study groups. Conclusion Based on the results, Drinking 500 cc/d kefir beverage had no significant effect on liver aminotransferases and metabolic indicators, except for HDL-C and fat-free mass in patients with NAFLD. Trial registration IRCT20170916036204N6 (2018/08/03).